Advanced transversal microradiography enables single section demineralization experiments. (January 2020) - Becker, Klaus; Engler, Katja; Trakiniené, Giedrė; Attin, Thomas; Attin, Rengin
Highlights: Quantification of mineral content in tooth hard tissue of >500 µm thickness. Microradiography calibration with a hydroxyapatite wedge and variable X-ray settings. No mechanical stress by grinding and polishing of the samples during the experiment. Relative differences to the normed basic measurements with single section technology. Abstract: Transversal Microradiography (TMR) is a method for quantifying the mineral density in enamel carious lesions. In the traditional procedure, X-ray images of 100 µm thin tooth sections are compared, whereby the grinding of the samples can produce undefined artefacts at the demineralized areas. In this study, the replacement of the usual aluminium step wedge by a continuous hydroxyapatite (HAp) wedge with an extended measuring range was validated, whereby, the mineral density of sections with >500 µm thickness could be quantified reproducibly. This enabled experiments with the single section technique: the sections were made from sound teeth and X-rayed immediately. After each experimental phase, a further image was taken, so that the changes in the mineral density of an object could be normalised to its baseline image at the end of the experiment. The results of the analysis with the traditional reference area differed significantly from the single-section analysis (p < 0.03; n = 8).